The Geopolitics Of The Thai Canal In Mahan And Kautilya's Perspective On Indonesia's Maritime Strategy In Southeast Asia - Ismaya Kenza Chalizta; Setiawibawa, Rachmat; Yulianto, Bayu Asih; Prakoso, Lukman Yudho (International Journal of Education, Vocational and Social Science, 2025)
The Thai Canal or Kra Canal project has become one of the most significant geopolitical issues in the Southeast Asian region because it has the potential to change the regional maritime balance of power. This article analyses the geopolitical dynamics of the Thai Canal through two major approaches, namely A.T. Mahan's Sea Power theory and Kautilya's Mandala theory. Mahan's approach emphasises the importance of control of sea lanes as a determinant of national power, while Kautilya highlights the hierarchical interactions between states based on interests and balance of power (raison d'état). By combining these two theories, this research seeks to assess how the Thai Canal project affects Indonesia's maritime strategy, particularly in the context of its strategic position towards the Strait of Malacca and the Indonesian Archipelago Sea Route (ALKI). The analysis shows that the Thai Canal has the potential to shift international trade flows from the Strait of Malacca to the Andaman Sea, resulting in changes to the geopolitical configuration of the region. Based on Mahan's perspective, this condition requires Indonesia to strengthen its control over ALKI II and III to maintain its strategic role in the global trade route. Meanwhile, in Kautilya's perspective, Indonesia needs to implement balanced diplomacy between major powers such as China and the United States to maintain regional stability and national interests. Overall, this article emphasises the importance of synergy between maritime power and regional diplomacy as a basis for Indonesia to respond to the new geopolitical dynamics triggered by the Thai Canal.